Centro de Reabilitação Física e Sensorial : a arquitetura como parte do processo de reabilitação - Poletto, Márcia Penz (2022)
This work is a social reflection on the way we look at part of the population that has some type of limitation and has their lives changed as a result. Disability is part of the human condition. We are all subject to disability, whether temporary or permanent. The loss of any of the body's functions, even temporarily, has a great impact on an individual, so that he loses much of his independence and freedom. Consequently, the importance of a space destined to the rehabilitation of this part of the population is perceived, based on the analysis of the different users who use the spaces and the difficulties that each one has. In recent years, Brazil has been investing in accessibility laws to support the disabled, bringing important advances to society. It is our obligation to provide adequate spaces to guarantee total quality of life for this part of the population. Attributing greater visibility to the theme and emphasizing its importance in the integration of community life.